Improving Mechanical Properties of Low-Quality Pure Aluminum by Minor Reinforcement with Fine B4C Particles and T6 Heat Treatment - Maxat Abishkenov; Ilgar Tavshanov; Nikita Lutchenko; Nursultan Amanzholov; Daniyar Kalmyrzayev; Zhassulan Ashkeyev; Kayrosh Nogaev; Saltanat Kydyrbayeva; Assylbek Abdirashit (Applied Sciences)
Pure aluminum, due to its inherent low strength and softness, is unsuitable for most structural applications. However, unlike many aluminum alloys, pure aluminum exhibits high ductility and is often free from expensive alloying elements. This makes it a promising candidate for minor reinforcement to produce cost-effective composites with an optimal balance of strength and ductility. This study assesses the possibility of improving the mechanical performance of pure aluminum specimens by minor reinforcement (~0.36 wt. %) with fine B4C particles and T6 heat treatment. The composites were obtained using ultrasonic-assisted stir casting and were characterized by assessing their density, microhardness, yield strength (YS), ultimate tensile strength (UTS), and elongation. Light microscopy (LM), scanning electron microscopy (SEM), energy-dispersive spectroscopy (EDS), and X-ray diffraction (XRD) tests were conducted to investigate the presence and distribution of reinforcing particles in the Al matrix. Minor reinforcement of ~0.5–2 μm with B4C particles without/with subsequent T6 heat treatment resulted in an increase in microhardness by 71.45% and 143.37% and UTS by 71.05% and 140.16%, respectively, while the elongation values of the specimens decreased to 51.98% and 42.38%, respectively, compared with the adopted initial matrix Al specimen.